1994
DOI: 10.1029/93jb02663
|View full text |Cite
|
Sign up to set email alerts
|

The root zones of oceanic hydrothermal systems: Constraints from the Samail ophiolite (Oman)

Abstract: The Cretaceous Samail ophiolite in Oman exposes an almost complete, 500‐km‐long, along‐axis section of oceanic crust, providing a unique opportunity to study the geometry, physical conditions, and effects of the hydrothermal circulation that fed the volcanic‐hosted massive‐sulfide deposits. These fossil discharge zones are rooted in the sheeted‐dike complex, down to the transition zone with the plutonic sequence. The sheeted‐dike complex as a whole was affected by greenschist‐facies metamorphism (albite, actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 25 publications
5
62
1
Order By: Relevance
“…It was recognized (Richardson et al 1987) that the extreme phase reduction of the epidosites might be the product of intense metasomatic alteration of the dykes under open-system conditions as envisaged by Korzhinskii (1959Korzhinskii ( , 1965. After their discovery in Troodos, epidosites were identified and described in several other ophiolites, the Josephine ophiolite in California/Oregon (Harper et al 1988 and related papers), the Semail ophiolite in Oman (Nehlig & Juteau 1988;Nehlig et al 1994) the Pindos ophiolite in Greece (Valsami & Cann 1992) and the Solund ophiolite in Norway (Fonneland-Jorgensen et al 2005). Epidosites have only rarely been found in the modern oceans, but have been dredged from the fore arc of the Tonga Arc (Banerjee et al 2000;Banerjee & Gillis 2001) and have been reported in rocks dredged from the Mid-Atlantic Ridge at 30°N (Shand 1949;Quon & Ehlers 1963).…”
Section: Epidosite Zones: Previous Workmentioning
confidence: 99%
See 4 more Smart Citations
“…It was recognized (Richardson et al 1987) that the extreme phase reduction of the epidosites might be the product of intense metasomatic alteration of the dykes under open-system conditions as envisaged by Korzhinskii (1959Korzhinskii ( , 1965. After their discovery in Troodos, epidosites were identified and described in several other ophiolites, the Josephine ophiolite in California/Oregon (Harper et al 1988 and related papers), the Semail ophiolite in Oman (Nehlig & Juteau 1988;Nehlig et al 1994) the Pindos ophiolite in Greece (Valsami & Cann 1992) and the Solund ophiolite in Norway (Fonneland-Jorgensen et al 2005). Epidosites have only rarely been found in the modern oceans, but have been dredged from the fore arc of the Tonga Arc (Banerjee et al 2000;Banerjee & Gillis 2001) and have been reported in rocks dredged from the Mid-Atlantic Ridge at 30°N (Shand 1949;Quon & Ehlers 1963).…”
Section: Epidosite Zones: Previous Workmentioning
confidence: 99%
“…The major element chemistry of rocks from epidosite zones shows the wide range in composition expected from the changing mineralogy (Richardson et al 1987;Harper et al 1988;Nehlig et al 1994;Bettison-Varga et al 1995). All of the rocks within epidosite zones, including the whole range from diabase to epidosite, are strongly depleted in Cu, Zn and Mn by between 50% and 90%, with Cu the most depleted and Mn the least (Richardson et al 1987;Harper et al 1988;Nehlig et al 1994;Bettison-Varga et al 1995). Jowitt et al (2012) (Bickle & Teagle 1992;Bickle et al 1998).…”
Section: Epidosite Zones: Previous Workmentioning
confidence: 99%
See 3 more Smart Citations